طبيعة قواعد القانون الدولي الإنساني في قضاء محكمة العدل الدولية - شوقــــي, سميـــــر (revue mofakir, 2018)
إن الفقه في مجمله، يؤكد أن قواعد القانون الإنساني، هي قبل كل شيء لها طابع آمر، كما تضمنته المادة 53 من اتفاقية فيينا لقانون المعاهدات لسنة 1969. غير ان محكمة العدل الدولية لم تصل بعد إلى اعتبار القانون الإنساني ضمن القواعد الآمرة، بالرغم أن الفرصة كانت مواتية لها في العديد من القضايا والآراء الاستشارية التي عرضت عليها وتناولت بمناسبتها تحليل قواعد القانون الإنساني أو قانون حقوق الإنسان بشكل أعم. إنّ دراسة شاملة للقضايا التي تطرقت فيها محكمة العدل الدولية إلى قواعد القانون الإنساني، والتي حللت فيها الطبيعة القانونية "العليا" لتلك القواعد تثبت بالفعل أن المحكمة كانت تتجنب وصف القانون الإنساني بصفة القواعد الآمرة، والاكتفاء بإبراز الطبيعة المطلقة لتلك القواعد والالتزامات الناشئة عنها تحت مسميات ومصطلحات متنوعة، ولكنها لم تجرئ على إلحاق صفة القاعدة الآمرة بالقانون الإنساني ولو لمرة واحدة ؟ وهو ما يؤكد بشكل عام تمسك المحكمة بفكرة السيادة وسلطان الإرادة في القانون الدولي.   Summary  : The jurisprudence in its entirety, confirms that the rules of humanitarian law, is first and foremost a commanding character, as the contents of Article 53 of the Vienna Convention on the Law of Treaties of 1969. However, the International Court of Justice has not yet reached the considered humanitarian law within the peremptory norms, although that opportunity were favorable in many of the issues advisory opinions offered by Bmanasptha addressed the rules of humanitarian law analysis or, more generally, human rights law. The comprehensive study of the issues in which the International Court of Justice touched on the rules of humanitarian law, which analyzed the "Supreme" the legal nature of those rules already shown that the Court was to avoid description humanitarian law as peremptory norms, and only highlight the absolute nature of those rules and obligations arising there from under the names and terms variety, but they did not dare to inflict recipe jus humanitarian law Qaeda even once? Which confirms the generally hold court with the idea of sovereignty and authority will in international law.